Studi Literatur Analisis Dugaan Luluh Energi Pada Tube Baja A53-Grade B - Sahlan Sahlan (Sekolah Tinggi Teknik - PLN, 2016)
The Importance of considering the literature of study the effect of different boundary conditions, strain-rate effects, and the influence of inertia in predecting the response of the such systems is demonstrated Under Impact conditions it is shown that a cluster of such tubes is subjectd to a shock wave which travels through the system. These experimental results compare favorably with numerical-structural shock-wave-thoery prediction.